Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Atmosfir Cafe Terhadap Keputusan Pembelian Konsumen Studi Kasus Pada Customer Generasi Z Di Coffee Shop 11:12 - Shofa, Almas Nazhifan; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The increasing habit of people consuming coffee, especially Generation Z, has encouraged the Indonesian coffee industry to grow rapidly in recent years. The purpose of this case study is to see how product quality, service quality, and cafe atmosphere influence the purchasing decisions of Generation Z customers at Coffee Shop 11:12. This research was conducted quantitatively using an explanatory research approach. Since the population size is unknown, the sample consisted of 80 individuals belonging to the late Generation Z. The sample size was calculated using Malholtra's formula. Data was analyzed using multiple linear regression after being collected through a questionnaire. The results of the study indicate that product quality has a positive effect but does not influence purchasing decisions, while service quality and café atmosphere have a significant positive influence. Keywords: Product Quality, Service Quality, Café Atmosphere, Purchasing Decision